Explorations of the nonheme high-valent iron-oxo landscape: crystal structure of a synthetic complex with an [FeIV2(μ-O)2] diamond core relevant to the chemistry of sMMOH. (16th February 2022) - Rohde, Gregory T.; Xue, Genqiang; Que, Lawrence
Abstract : A synthetic mimic for the putative FeIV2O2 diamond core of sMMOH-Q . Abstract : Methanotrophic bacteria utilize methane monooxygenase (MMO) to carry out the first step in metabolizing methane. The soluble enzymes employ a hydroxylase component (sMMOH) with a nonheme diiron active site that activates O2 and generates a powerful oxidant capable of converting methane to methanol. It is proposed that the diiron(ii ) center in the reduced enzyme reacts with O2 to generate a diferric-peroxo intermediate called P that then undergoes O–O cleavage to convert into a diiron(iv ) derivative called Q, which carries out methane hydroxylation. Most (but not all) of the spectroscopic data of Q accumulated by various groups to date favor the presence of an FeIV2(μ-O)2 unit with a diamond core. The Que lab has had a long-term interest in making synthetic analogs of iron enzyme intermediates. To this end, the first crystal structure of a complex with a Fe III Fe IV (μ-O)2 diamond core was reported in 1999, which exhibited an Fe⋯Fe distance of 2.683(1) Å. Now more than 20 years later, a complex with an FeIV2(μ-O)2 diamond core has been synthesized in sufficient purity to allow diffraction-quality crystals to be grown. Its crystal structure has been solved, revealing an Fe⋯Fe distance of 2.711(4) Å for comparison with structural data for related complexes with lower iron oxidation states.